Surrounding green, air pollution, traffic noise exposure and non-accidental and cause-specific mortality - Klompmaker, Jochem O.; Hoek, Gerard; Bloemsma, Lizan D.; Marra, Marten; Wijga, Alet H.; van den Brink, Carolien; Brunekreef, Bert; Lebret, Erik; Gehring, Ulrike; Janssen, Nicole A.H. (Environment international, 2020)
•Surrounding green, air pollution and traffic noise were moderately correlated.•Surrounding green was not significantly associated with non-accidental mortality.•Analyses restricted to non-movers did not change the findings.•Air pollution was not significantly associated with non-accidental mortality. Most previous studies that investigated associations of surrounding green, air pollution or traffic noise with mortality focused on single exposures. The aim of this study was to evaluate combined associations of long-term residential exposure to surrounding green, air pollution and traffic noise with total non-accidental and cause-specific mortality. We linked a national health survey (Public Health Monitor, PHM) conducted in 2012 to the Dutch longitudinal mortality database. Subjects of the survey who were 30 years or older on 1 January 2013 (n = 339,633) were followed from 1 January 2013 till 31 December 2017. We used Cox proportional hazard models to evaluate associations of residential surrounding green (including the average Normalized Difference Vegetation Index (NDVI) in buffers of 300 m and 1000 m), annual average air pollutant concentrations (including particulate matter (PM10, PM2.5), nitrogen dioxide (NO2)) and traffic noise with non-accidental, circulatory disease, respiratory disease, lung cancer and neurodegenerative disease mortality. We observed 26,886 non-accidental deaths over 1.627.365 person-years of follow-up. Surrounding green, air pollution and traffic noise exposure were not significantly associated with non-accidental or cause-specific mortality. For non-accidental mortality, we found a hazard ratio (HR) of 0.99 (0.98, 1.01) per IQR increase in NDVI 300 m, a HR of 0.99 (95% CI: 0.97, 1.01) per IQR increase in NO2, a HR of 0.98 (0.97, 1.00) per IQR increase in PM2.5 and a HR of 0.99 (95% CI: 0.97, 1.01) per IQR increase in road-traffic noise. Analyses restricted to non-movers or excluding subjects aged 85+ years did not change the findings. We found no evidence for associations of long-term residential exposures to surrounding green, air pollution and traffic noise with non-accidental or cause-specific mortality in a large population based survey in the Netherlands, possibly related to the relatively short follow-up period.